A Lifecourse Approach to Health Development: Implications for the Maternal and Child Health Research Agenda - Russ, Shirley A.; Larson, Kandyce; Tullis, Ericka; Halfon, Neal (Maternal and child health journal, 2014)
Lifecourse-informed models of health fundamentally challenge simple biomedical models, introducing new ways of thinking about how diseases develop. This paper considers the broad implications of lifecourse theory for the maternal and child health (MCH) research agenda. The Lifecourse Health Development model provides an organizing framework for a synthesis of the existing literature on lifecourse health and identification of gaps in knowledge. Priority areas identified for MCH research in order to close these knowledge gaps include: epigenetic mechanisms and their potential mutability; peri-conception as a critical and sensitive period for environmental exposures; maternal health prior to pregnancy; the role of the placenta as an important regulator of the intra-uterine environment; and ways to strengthen early mother–child interactions. Addressing knowledge gaps will require an emphasis on longitudinal rather than cross-sectional studies, long-term (lifetime) rather than short-term perspectives, datasets that include socio-demographic, biologic and genetic data on the same subjects rather than discipline-specific studies, measurement and study of positive health as well as disease states, and study of multi-rather than single generational cohorts. Adoption of a lifecourse-informed MCH research agenda requires a shift in focus from single cause-single disease epidemiologic inquiry to one that addresses multiple causes and outcomes. Investigators need additional training in effective interdisciplinary collaboration, advanced research methodology and higher-level statistical modeling. Advancing a life course health development research agenda in MCH will be foundational to the nation’s long-term health.